The effect of long range order on the activation energy for atomic migration in NiAl alloys; resistivity study - Ko, HJ; Hong, KT; Kaufmann, MJ; Lee, KS (KLUWER ACADEMIC PUBL, 2002)
The influence of the degree of long range order (S) on the migration energy in NiAl was investigated by electrical resistivity and X-ray diffraction. Iron (12at.%) was over-alloyed to the stoichiometric NiAl in order to decrease the order-disorder transition temperature.(NiAl12Fe) The degree of LRO in NiAl12Fe decreased gradually as temperature increased. The activation energies for migration of iron in NiAl12Fe (Q(A)(Fe*)) that were measured from the temperature dependence of jumping frequency (1/tau(Fe*)) were 1.42 +/- 0.19 eV, 1.35 +/- 0.18 eV, 1.16 +/- 0.06 eV for the alloys quenched from 1073 K, 1273 K, and 1473 K respectively. The activation energies for migration of excess vacancy (Q(A)(v*)) in NiAl single crystal, were 1.55 +/- 0.02 eV for the specimen quenched from 1473 K and 1.40 +/- 0.11 eV for one quenched from 1673 K. The degree of LRO (S) in single crystalline NiAl calculated from the result of Hughes Lautensclager, Cohen and Brittain, J. Appl. Phys. 42 (1971) 3705 seems to be consistent with this decreasing tendency in the activation energy. The reduction of the degree of LRO (S) can explain these variations in the migration energy as the Girifalco's model. (C) 2002 Kluwer Academic Publishers.
Keywords: DIFFUSION; NI3AL; PHASES; DISORDER; SYSTEM; FE3AL